Gaseous Vapor Emission (GVE) Technique for Detection of Petrol Adulteration at Point of Sale (POS) Terminals - Onyishi, Donatus Uchechukwu; Ejofodomi, O’tega (International Journal of Chemical and Process Engineering Research, 2020)
Adulteration of petrol is difficult to detect at point of sale terminals (POS) because current detection methods require chemical laboratory experiments to measure parameters such as density, API gravity and evaporation point, are extremely bulky, time-consuming, and require experienced technicians to operate. This paper explores a new technique for adulteration detection at POS terminals, known as Gaseous Vapor Emission (GVE). GVE was performed on 1 L of pure petrol obtained from a Nigerian National Petroleum Corporation (NNPC) Retail Outlet, using a portable Petroleum Product Volume Estimator and Tracker (PPVET). Results showed that pure petrol gave a peak methane emission in 30 seconds, and a peak butane emission in 60 seconds. In an enclosed space of 19,000 cm3, a sample of pure petrol emits 4,466,841-5,308,924 ppm of methane, 12.23-19.09 ppm of LPG, and 216,667-383,408 ppm of butane. GVE correctly identified the petrol sample as being pure, by verifying the presence of the characteristic methane and butane emission peaks, and the technique can be used at POS terminals to test for petrol adulteration. Future work includes the expansion of the GVE chemical signature for petrol to include other gases in addition to methane, LPG, and butane, the ability to utilize GVE in detecting adulterated petrol, and when present, estimation of the level of adulteration, as well as accurate identification of the adulterant used.